Moisture sorption isotherms and isosteric heat sorption of habanero pepper (Capsicum chinense) dehydrated powder - Luna-Flores, M.; Pena-Juarez, M. G.; Bello-Ramirez, A. M.; Telis-Romero, J. [UNESP]; Luna-Solano, G.; Carcel, J. A.; Clemente, G.; GarciaPerez, J. V.; Mulet, A.; Rossello, C. (Univ Politecnica Valencia, 2018)
Moisture sorption isotherms of the habanero pepper powder were determined using the Dynamic Vapor Sorption (DVS) method at 20, 25, 35, 45 and 55 degrees C in a range of water activity from 0.10 to 0.90 at which the processes of drying, packing and storage of habanero pepper are developed. The sorption capacity decreased with increasing temperature at a given water activity and the sorption isotherms showed a sigmoid form (Type II). The hysteresis phenomenon was observed in the sorption isotherms at all temperatures studied and it was more pronounced at temperatures high. The experimental sorption curves were fitting to the GAB, BET and Oswin models. It was concluded that the models that best describe the adsorption and desorption data for habanero pepper dehydrated powder were the GAB and Oswin models. The isosteric heat of water sorption was calculated with the moisture content data in equilibrium. The desorption isotherms present a higher isosteric heat in relation to the adsorption isotherms. In both, the isosteric heat decreased as the moisture content increased.
Keywords: Habanero pepper dehydrated powder; Convective drying; Moisture sorption isotherms; Mathematic models